Análisis de riesgos bajo un modelo de lógica difusa en la construcción del proyecto hidroeléctrico Hidroituango (2021)
The purpose of this document is to analyze and quantify the risks of a hydroelectric project in Colombia, by assessing the relationships that can be generated between the different types of risks. For this, the HidroItuango project is used as a case study, which is developed by Empresas Públicas de Medellín (EPM), a project that has presented a great variety of interrelated risks and for whose analysis an assessment is necessary based on uncertainty and impact. For the risk analysis, risk assessments and expert judgments were used, instead of probabilistic reasoning, and a fuzzy scoring tool was proposed, where the methodology used uses a multi-criteria decision analysis, which allows to understand easily and Flexible project risk analysis.